Azithromycin (Sumamed®) in empiric treatment of nosocomial pneumonia in upper digestive tract cancer patients - Szawłowski, Andrzej; Szpakowski, Marek (Contemporary Oncology/Współczesna Onkologia, 2003)
Septic complications are the most frequent and potentially lethal complications among patients treated for tumours. These kind of complications are very frequent especially among patients treated due to upper digestive tract cancers (surgical or multiapproach treatment). Respiratory tract infection, including pneumonia, is third most frequent of all infections occurring among patients undergoing surgical treatment. It is not proved that antibiotics are effective in prevention of respiratory tract septic complications. In patients with septic pulmonary complications great clinical and pharmaeconomical importance is rational therapy with antibiotics. Azithromycin proved to be effective cure for environmental pneumonia. There has been presented a preliminary research on effectiveness of azithromicin in the treatment of septic pneumonia among patients treated for upper digestive tract cancers.